C++ : The Complete Reference - Schildt, Herbert (McGraw-Hill, 2003)
This covers everything from keywords, syntax, and libraries, to advanced features such as overloading, inheritance, virtual functions, namespaces, templates, and RTTI—plus, a complete description of the Standard Template Library (STL)